Chemical composition of treated agarwood (Aquilaria malaccensis) essential oil - Hezelin Elayana, Shaian (2022)
Agarwood oil has a high value due to its widespread use in industries including perfumes, pharmaceuticals, and traditional medicine. The aroma strength and uniqueness of the agarwood oil depend on sesquiterpenes and sesquiterpenoid contents. Not much is known about the outcome of exposing agarwood oil to heat, ultraviolet light, oxygen gas flow, and sunlight over a significant time (days), producing sesquiterpenes and sesquiterpenoid contents to increase the woody aroma. This study aims to analyze the chemical compositions of the commercial and laboratory agarwood oil (Aquilaria malaccensis) extracted by hydro distillation (HD) method and investigate how the treatment techniques affect the agarwood oil chemical compositions using the chromatography method. Finally, the study evaluated the best parameter contributing to the production of high-quality A. malaccensis oil. The problem was addressed by exposing the commercial and laboratory A. malaccensis oil through four parameters treatment techniques which are constant 40 oC heat exposure, exposure through the ultraviolet light, set at a UV-B wavelength of 365 nm, exposure to oxygen gas, set at a constant flow of 15L/mins, and sunlight over three, seven, fourteen, twenty and thirty days. Then, gas chromatographic flame ionization detection (GC-FID) and gas chromatographic-mass spectrometry (GC-MS) were used to analyze the chemical compositions. From this study, the percentage yields of laboratory A. malaccensis oils obtained from HD was 0.15 %, with an extraction time of 72 hours. Four groups of chemical compositions in A. malaccensis oil were identified using GC analyses, namely carboxylic acids, other compounds, sesquiterpenes, and sesquiterpenoid. In conclusion, 29–51 compounds were obtained in treated laboratory A. malaccensis oil and 17–56 compounds in treated commercial A. malaccensis oil, both dominated by sesquiterpenoid compounds. Six compounds were identified in all samples in this study: n-hexadecanoic acid, epi-α-cadinol, α-eudesmol, guaia-1(10),11-dien-9-one, selina-4,11-dien-14-oic acid, and karanone. Evaluation of exposure to oxygen flow at 15L/mins in seven days showed the best parameter for producing the high-quality commercial A. malaccensis oil, supported by the highest total percentages of sesquiterpenes and sesquiterpenoid compound (71.17 %) and the highest mean value (1.52). Meanwhile, the parameter that contributed to the high quality of laboratory A. malaccensis oil was treating oil to sunlight for three days, supported by the highest total percentages of sesquiterpenes and sesquiterpenoid compound (42.76 %) and the highest mean value (0.93). The results showed an increase in sesquiterpenes and sesquiterpenoid contents from 20.01 % to 42.76 %, indicating that the treatment techniques on laboratory A. malaccensis oil did increase the total amounts as desired. Hence, oxygen gas flow in seven days and sunlight treatment in three days could be applied to A. malaccensis oil to obtain essential oil enriched with targeted bioactive molecules. These findings could be used as an alternative approach to preparing the high-quality agarwood essential oil profiles from the genus Aquilaria which are presently lacking.